Moraxella catarrhalis pneumonia in an AIDS patient: A case report - Cheepsattayakorn A. (2014)
Moraxella catarrhalis pneumonia, although in the immunocompromised patients is very uncommon for community-acquired pneumonia (CAP). It demonstrates a potential pathogen with high mortality when the presence of heavy numbers of organisms, intracellularly and extracellularly, in the sputum Gram's stained smears confirmed by cultures. In 2007, the authors reported a case of a 28-year-old Thai single male patient with acquired-immunodeficiency syndrome (AIDS) and Moraxella catarrhalis pneumonia who dramatically responded to two weeks of oral Amoxyclav (Amoxycillin trihydrate 500 milligrams + Clavulanic acid (Potassium clavulanate) 125 milligrams) treatment at 625 milligrams every 8 hours and then discharged. The present case report describes clinical and initial chest roentgenographic presentations of Moraxella catarrhalis pneumonia in AIDS patient. The importance of chest roentgenographic pictures, CD4/CD8-T lymphocyte ratio, sputum Gram's stainings, cultures with susceptibility testing in establishing a diagnosis, and protective vaccine are discussed.